Penerapan Terapi Tertawa Pada Lansia Dengan Hipertensi Di Puskesmas Tiban Baru Kota Batam - Fitriany Suangga; Siska Natalia; Ameliana Olifia Helwend (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Hypertension is a chronic disease which is one of the causes of death. Based on data from the Indonesian Ministry of Health in 2022, the prevalence of hypertension in Indonesia was 32.7%, an increase compared to the prevalence of hypertension in 2021 which was 25.8%. Old age is the final stage of development in which humans experience various health problems and are at high risk of dangerous diseases, one of which is hypertension. The Batam City Health Service noted that hypertension occurs more often in elderly people aged 60-70 years. Meanwhile, the number of elderly people suffering from hypertension aged over 60 years at the Tiban Baru Community Health Center is 402 cases. Many non-pharmacological therapies are used to lower blood pressure, one of which is laughter therapy. Laughter lowers blood pressure by calming the body and reducing stress hormones. The aim of this community service activity is to increase knowledge about hypertension and treating hypertension with non-pharmacological methods using laughter therapy. The methods used are lectures, discussions, questions and answers and demonstrations. The results of 20 elderly people showed an average blood pressure of 159.75/92.55 mmHg before laughing therapy, while after therapy the average blood pressure was 123.55/80.25mmHg.